Digital Technologies in Craniomaxillofacial Surgery (Springer New York, 2018)
Digital technologies are changing the way that surgeons operate. They are revolutionizing the ability of surgeons to visualize, plan, and create rapid prototyped models and patient- specific implants for the broad disciplines of ENT, plastic, oral and maxillofacial surgeons. This book provides information on the latest digital technologies available for craniomaxillofacial surgery, discussing how this technology allows for preplanned procedures with improved and superior outcomes. Rather than improvise during surgery, surgery and its procedures can be preconceptualized with superior outcomes and decreased patient morbidity.